Physical culture and patriotic education of youth as an element of preparation for military service - Rogozhnikova R.A.; Belova G.B.; Filatov A.V.; Sergeev N.N. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the features of sports and patriotic education in preparing young people for military service. Methods and structure of the study. In the period from 2023 to 2024, a scientific study was conducted, the object of which were young men of draft age (hereinafter referred to as young men) living in the city of Perm and the Perm region. All subjects underwent an assessment of their physical fitness and the degree of development of their main physical characteristics. Additionally, as part of the study, the experience of participating in competitions and events of military and sports orientation with patriotic themes, held in Perm and the Perm region, was analyzed. Results and conclusions. The decline in health and physical fitness of pre-conscription age young men is becoming noticeable due to insufficient physical activity in physical education classes at educational institutions. There are unfavorable changes in the military-patriotic education of the new generation. One of the problems in preparing young people for military service is the fading of patriotism and the prevalence of consumer interests. Physical and patriotic education plays a key role in preparing young men for military service. The practice of military-sports education of young people in Perm and the Perm Territory is a modern and relevant approach.